Thoracic surgery in the non-intubated spontaneously breathing patient - Grott, Matthias; Eichhorn, Martin E.; Eichhorn, Florian; Schmidt, Werner; Kreuter, Michael; Winter, Hauke (Respiratory research, 2022)
The interest in non-intubated video-assisted thoracic surgery (NIVATS) has risen over the last decade and numerous terms have been used to describe this technique. They all have in common, that the surgical procedure is performed in a spontaneously breathing patient under locoregional anaesthesia in combination with intravenous sedation but have also been performed on awake patients without sedation. Evidence has been generated favouring NIVATS compared to one-lung-ventilation under general anaesthesia.
Gesehen am 01.02.2023